Numerical Evaluation of Human Body Near Field Exposure to a Vehicular Antenna for Military Applications - Colella, Micol; Biscarini, Marianna; de Meis, Marco; Patrizi, Roberto; Ciallella, Tino; Ferrante, Daniele; De Gaetano, Alessandro; Capuano, Marco; Pellegrino, Giovanni; Martini, Emanuele; Cavagnaro, Marta; Apollonio, Francesca; et al. (Frontiers in Public Health, 2022)
Abstract Background: The use of electromagnetic (EM) technologies for military applications is gaining increasing interest to satisfy different operational needs, such as improving battlefield communications or jamming counterparts’ signals. This is achieved by the use of high-power EM waves in several frequency bands (e.g., HF, VHF, and UHF). When considering military vehicles, several antennas are present in close proximity to the crew personnel, which are thus potentially exposed to high EM fields. Methods: A typical exposure scenario was reproduced numerically to evaluate the EM exposure of the human body in presence of an HF vehicular antenna (2 – 30 MHz). The antenna was modeled as a monopole connected to a 3D polygonal structure representing the vehicle. Both the EM field levels in the absence and in the presence of the human body as well as the Specific Absorption Rate (SAR) values were calculated. The presence of the operator, partially standing outside the vehicle, was simulated with the virtual human body model Duke (Virtual population, v. 3). Several exposure scenarios were considered. The presence of a protective helmet was modeled as well. Results: In the area usually occupied by the personnel, E-field intensity radiated by the antenna can reach values above the limits settled by international safety guidelines. Nevertheless, local SAR values induced inside the human body reached a maximum value of 14 mW/kg, leading to whole body averaged and 10g averaged SAR values well below the corresponding limits. Conclusion: A complex and realistic near-field exposure scenario of the crew of a military vehicle was simulated. The obtained E-field values radiated in the free space by a HF vehicular antenna may reach values above the safety guidelines reference levels. Such values are not necessarily meaningful for the exposed subject. Indeed, SAR and E-field values induced inside the body remain well below safety limits.